Asuhan Kebidanan Komprehensif pada Ny. M di Puskesmas Slawi Kabupaten Tegal Tahun 2023 (Studi Kasus Anemia Ringan dengan Penerapan Pijat Oksitosin) - Nabila Syafa Gunawan; Seventina Nurul Hidayah; Nora Rahmanindar (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
The Maternal Mortality Rate (MMR) in Tegal Regency has increased drastically since the Covid-19 pandemic. The number of maternal deaths in Tegal Regency in 2021 and 2022 was recorded at 30 deaths each year. Meanwhile, in 2023 until the end of June, there were 9 cases of maternal deaths. Based on data obtained from the Slawi Health Center in 2023, there were 142 cases, including high-risk pregnant women, with causes of age, pregnancy spacing, maternal height less than 145 cm, grandemultipara, KEK, hypertension, history of CS, gemelli, and fetal abnormalities. For anemia itself, there were 34 cases. The purpose of this case study is to obtain a real picture and experience in providing comprehensive midwifery care to Mrs. M at the Slawi Health Center, Tegal Regency in 2023 (Case Study of Mild Anemia with the Application of Oxytocin Massage). This study uses a case study approach. The subjects of the study were pregnant women Mrs. M is 29 years old with Mild Anemia. Data was taken from September to November 2023. Data was taken using interviews, observations, and documentation, the results during pregnancy the subject accepted to have an Hb check, and the results of the subject at the 3rd visit Hb increased and was normal. Pregnant women with anemia can cause bleeding, premature birth, and death. Suggestion: If the same case is found, collaboration with a doctor is needed during pregnancy until postpartum, in addition it is necessary to involve the family, especially children during pregnancy and after the baby is born.